Simplify (x - y + 1) - (x + y - 1).

= x - y + 1 - x - y + 1

= (x - x) + (-y - y) + (1 + 1)

= -2y + 2

= (5x - 4) - (4x + 3)

= (5x - 4) + (-4x - 3)

= x - 7

= 2a - 13 - 9a - 2 + 7a + 3

= -12

= 5h - 3k

= a - [5b - (a - 3b + 2c + c - a + 2b + c)]

= a - [5b - (-b + 4c)]

= a - (5b + b - 4c)

= a - (6b - 4c)

= a - 6b + 4c

SOLUTION:

2m - [n - (m - 2n)].

2m - [n - m + 2n].

2m - n + m - 2n.

2m + m - n - 2n.

3m - 3n.

Question

Asked 2/17/2016 8:36:32 AM

Updated 2/17/2016 11:49:56 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by jeifunk [2/17/2016 11:49:29 PM], Edited by jeifunk [2/17/2016 11:49:50 PM], Edited by jeifunk [2/17/2016 11:49:56 PM]

Rating

3

{n - 1 - [n - 1 - (n - 1)]}

= {n - 1 - (n - 1 - n + 1)}

= {n - 1 - 0}

= n - 1

= {n - 1 - (n - 1 - n + 1)}

= {n - 1 - 0}

= n - 1

Added 2/17/2016 11:44:19 PM

This answer has been confirmed as correct and helpful.

simplify 11 - 2m-(n + 5+-m - 3n + 8)

Question

Not Answered

Updated 2/17/2016 9:00:28 AM

1 Answer/Comment

11 - 2m-(n + 5+-m - 3n + 8)

=(-2m + m)+(- n + 3n)+(11 +(-5)+(-8))

= - m + 2n - 2

=(-2m + m)+(- n + 3n)+(11 +(-5)+(-8))

= - m + 2n - 2

Added 2/17/2016 9:00:28 AM

This answer has been confirmed as correct and helpful.

27,911,482

questions answered

There are no comments.